AI IN HEALTHCARE ANALYTICS: TRANSFORMING PATIENT CARE AND OPERATIONAL EFFICIENCY - Gautam Ulhas Parab, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Artificial Intelligence has revolutionized healthcare analytics, transforming patient care delivery and operational management in healthcare institutions worldwide. This comprehensive article examines the integration of AI-driven analytics in healthcare settings, exploring its impact on clinical decision support, predictive analytics, and resource optimization. The article investigates how AI technologies enhance diagnostic accuracy, improve patient outcomes, and streamline operational efficiency while addressing critical privacy and security considerations. The findings demonstrate that AI implementation in healthcare has significantly improved clinical outcomes, operational workflows, and financial performance while necessitating robust security frameworks to protect sensitive patient information. This article provides insights into AI adoption in healthcare and its potential to shape the future of medical care delivery.